2015
DOI: 10.1371/journal.pone.0122866
|View full text |Cite
|
Sign up to set email alerts
|

Why Do You Dance? Development of the Dance Motivation Inventory (DMI)

Abstract: Dancing is a popular form of physical exercise and studies have show that dancing can decrease anxiety, increase self-esteem, and improve psychological wellbeing. The aim of the current study was to explore the motivational basis of recreational social dancing and develop a new psychometric instrument to assess dancing motivation. The sample comprised 447 salsa and/or ballroom dancers (68% female; mean age 32.8 years) who completed an online survey. Eight motivational factors were identified via exploratory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 41 publications
5
45
0
2
Order By: Relevance
“…A much discussed effect of dance is its power to increase well‐being, quality of life, and mood . However, in keeping with the framework outlined above, we propose that well‐being is a secondary effect of deeper biological effects caused by the functions of dance just as has been suggested for music (Fig.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…A much discussed effect of dance is its power to increase well‐being, quality of life, and mood . However, in keeping with the framework outlined above, we propose that well‐being is a secondary effect of deeper biological effects caused by the functions of dance just as has been suggested for music (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…300,303,304 Furthermore, being a professional artist/dancer can be a health hazard. [305][306][307][308][309][310][311][312] This suggests that there might be a healthy "dosage" and "treatment range" for engagement with any art.…”
Section: Dance Is For Experts Onlymentioning
confidence: 99%
“…Prior research on motivation for dance indicated that adults dance to improve their mood, fitness, self-confidence, and mastery and to socialize with others (Maraz, Kiraly, Urban, Griffiths, & Demetrovics, 2015). This research suggests that adults expect improvements in more than just the physical domain, yet there is very little research examining perceived or objectively measured cognitive, social, or emotional improvements associated with dancing.…”
mentioning
confidence: 99%
“…TMD-associated pain can affect one's performance on activities of daily life, psychosocial functioning, and quality of life 17 . Dance provides a tiring, but pleasant way to exercise that can improve the fitness level and encourage a more active lifestyle 18 . Pain intensity and fear of mandible movements play an important role in the decision to seek care for orofacial pain.…”
Section: Discussionmentioning
confidence: 99%